CRYSTAL LATTICE OF GALLIUM-GERMANIUM X-ANDALUSITE - Gorogotskoya L.I.; Litvin A.L.; Ostapenko S.S.; Sorokina S.L. (My University, 1990)
x-Andalusite is a widely occurring phase, generated at high water temperatures and vapor pressures in the system Al2O3-SiO2-H2O. However, the structure of its lattice is not easy to decipher because the crystals are very small (usually no more than 10 μm) and contain a multitude of defects. This obstacle was overcome by investigation of the Ga2O3-GeO2-H2O system (the mineralizer was HCl) which is a model system in petrology. Goniometric measurements allowed us to classify the habit of gallium-geramium x- andalusite crystals as pyramidal-prismatic due to the presence of the {100} and {110} prisms and the {111} pyramid. The content of OH groups was derived from valence balance in the formula and matches the estimate of hydroxyl content from IR spectra. Based upon the local valence balance and the anisotropic parameters, we concluded that the hydroxyl groups are randomly distributed over the positions of the O(4) atoms. Thus, the compound historically referred to as x- andalusite is a separate compound possessing greater structural similarity to sillimanite and mullite than to andalusite.